Unexplained Neonatal Cardiorespiratory Collapse at Five Minutes of Age - Sona Zaleta; Sarah Miller; Prashant Kumar (Case Reports in Pediatrics)
We report a case in which a term neonate suffered cardiorespiratory collapse at five minutes of age following an uncomplicated delivery and Apgar score of eight at one minute. Following prolonged cardiopulmonary resuscitation, the infant recovered well with no neurological deficit. Although sudden and unexpected postnatal collapse has been extensively described, this case does not fulfil its definition criteria. It provides a diagnostic challenge for clinicians and to the best of our knowledge is the first report of unexplained cardiorespiratory collapse at five minutes of age. The case serves as a timely reminder that cord gas analysis is recommended in all cases of potential fetal compromise and that Apgar scores should be used with caution as a predictor of neurological sequelae.